2013
DOI: 10.1091/mbc.e12-06-0481
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD9 links junctional adhesion molecule-A to αvβ3 integrin to mediate basic fibroblast growth factor–specific angiogenic signaling

Abstract: This paper describes a ternary protein complex consisting of junctional adhesion molecule-A (JAM-A), tetraspanin CD9, and αvβ3 integrin in endothelial cells. In this complex, CD9 links JAM-A to αvβ3 integrin to regulate basic fibroblast growth factor–specific mitogen-activated protein kinase activation, endothelial cell migration, and tube formation. Our findings contribute to a better understanding of the signaling events during angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…9. In this model we show the involvement of CD9 which acts as a scaffold protein (50) to tether adhesion molecules such as ␣v␤3 integrin (50), with which it co-localizes on sperm, and ␣5␤1. During capacitation and the AR when OVS are released and the ligands and their receptors are increased on sperm (37,38), receptor-ligand interactions are favored and facilitate fusion.…”
Section: Discussionmentioning
confidence: 97%
“…9. In this model we show the involvement of CD9 which acts as a scaffold protein (50) to tether adhesion molecules such as ␣v␤3 integrin (50), with which it co-localizes on sperm, and ␣5␤1. During capacitation and the AR when OVS are released and the ligands and their receptors are increased on sperm (37,38), receptor-ligand interactions are favored and facilitate fusion.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we as well as others, have shown that JAM-A associate with integrin a v b 3 on quiescent endothelial cells, and similar to platelets, it dissociates from the integrin upon activation of endothelial cells by growth factors or cytokines. 28,31,46 Furthermore, it has recently been shown that the association of JAM-A with the integrin a v b 3 on endothelial cells is via CD9. 46 Since platelets abundantly express CD9, it is possible that JAM-A associates with integrin a IIb b 3 via CD9 in platelets as well.…”
Section: Discussionmentioning
confidence: 99%
“…28,31,46 Furthermore, it has recently been shown that the association of JAM-A with the integrin a v b 3 on endothelial cells is via CD9. 46 Since platelets abundantly express CD9, it is possible that JAM-A associates with integrin a IIb b 3 via CD9 in platelets as well.…”
Section: Discussionmentioning
confidence: 99%
“…Because abnormal elevations of MMP-9 are detected in CD9-null wounds, this delayed epidermal migration may be attributed to excessive degradation of type IV collagen in the basement membrane at the wound site rather than to changes in the migrating keratinocytes themselves. 19 Moreover, because CD9 promotes endothelial cell migration and angiogenesis, 105,106 loss of CD9 might negatively affect angiogenesis at the wound site, additionally contributing to impaired epidermal migration and re-epithelialization. In summary, these data implicate tetraspanins CD151 and CD9 as important regulators of the wound healing process, indicating their role as potential therapeutic targets for pathological wound repair.…”
Section: Tetraspanins In Keratinocyte Migration During Wound Healingmentioning
confidence: 99%
“…105 In HUVECs, CD9 forms a ternary complex with avb3 integrin and junctional adhesion molecule A and positively regulates basic fibroblast growth factorinduced cell migration and tube formation following release of junctional adhesion molecule A and activation of MAPK. 106 GS-168AT2, a truncated form of CD9-partner 1 protein, which depletes cell surface CD151 and CD9, inhibits vascular endothelial growth factor-induced HUVEC migration and tube formation in vitro and attenuates tumor-associated angiogenesis in vivo. 107 Moreover, anti-CD9 antibody was shown to inhibit tumor progression in a human gastric cancer xenograft model via inhibition of both tumor growth and tumor-associated angiogenesis.…”
mentioning
confidence: 99%